2003
DOI: 10.1051/0004-6361:20030913
|View full text |Cite
|
Sign up to set email alerts
|

A study of the Mg II 2796.34 Å emission line in late–type normal and RS CVn stars

Abstract: Abstract.We carry out an analysis of the Mg  2796.34 Å emission line in RS CVn stars and make a comparison with the normal stars studied in a previous paper (Paper I). The sample of RS CVn stars consists of 34 objects with known HIPPARCOS parallaxes and observed at high resolution with IUE. We confirm that RS CVn stars tend to possess wider Mg  lines than normal stars having the same absolute visual magnitude. However, we could not find any correlation between the logarithmic line width log W • and the abs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The Mg ii k line fluxes were obtained through the method described in Cardini et al (2003), which consists in a direct integration of the observed profiles, as measured above the photospheric flux level. The estimated relative uncertainty on the measured fluxes is AE15%.…”
Section: Sample and Data Processingmentioning
confidence: 99%
“…The Mg ii k line fluxes were obtained through the method described in Cardini et al (2003), which consists in a direct integration of the observed profiles, as measured above the photospheric flux level. The estimated relative uncertainty on the measured fluxes is AE15%.…”
Section: Sample and Data Processingmentioning
confidence: 99%
“…In addition to normal stars, we consider here a sample of 29 very active evolved stars of the RS CVn type. They have been selected following the criteria given in Cardini et al (2003) (hereafter Paper II) and further selected following the criteria illustrated above.…”
Section: Sample Of Starsmentioning
confidence: 99%